Suggestion - Ross, Alice May (My University, 1903)
Introduction: It is not the purpose here to discuss the relation of the concious and subconcious minds, but rather the moral effects of suggestions given with the intention of making a change in the thought channels, and also unconcious suggestions. It is becoming more and more an acknowledged fact that the human life is molded, not by environment in the old sense, but by such suggestions as are offered in the surroundings. These unconscious suggestions are constantly being pushed upon the mind, from baby-hood days to the grave. The babe is laying up memories in its subconcious mind that we know nothing of, and that may or may not be given to others, or even realized by the concious mind, still these all have their effect upon forming character. The youth during his college days, gains knowledge not only from books and instructors, but he is receiving impressions on his subjective mind that can never be erased. Acts, words and sometimes it seems almost the thoughts of those around him are written indelibly upon this mysterious mind. Parents and teachers do not realize the influence of suggestions given to the subconcious minds of children upon their future actions and character or there would be a reform in the manner of training children in the home and school. The subjective mind of the child has not been trained to accept or reject what may be presented to it, and so is very susceptible to training by suggestions.
Citation: Ross, Alice May. Suggestion. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Concious Mind; Unconcious Mind; Education Reform; Theses